2011
DOI: 10.1038/eye.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient outcomes after implantation of Visian toric implantable collamer lens and iris-fixated toric phakic intraocular lens

Abstract: Purpose We compared visual and refractive outcomes after implantation of Visian toric implantable collamer lenses (toric ICLs) and iris-fixated toric pIOLs (toric Artisans). Patients and methods A comparative retrospective analysis was performed. Toric ICLs were implanted into 30 eyes of 18 patients, and toric Artisans into 31 eyes of 22 recipients. We measured the logarithms of the minimum angle of resolution of uncorrected visual acuity (logMAR UCVA), logMAR of best spectaclecorrected corrected VA (logMAR BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…No significant difference was observed between groups (RR = 1.20; 95% CI, 0.24 to 6.00; P  = .82; I 2  = 37.5%) (Figure 6). Omitting Lee et al [33], this result was similar (RR = 1.53; 95% CI, 0.23 to 10.12; P  = .66; I 2  = 45.1%). By Begg's and Egger's tests, there was no evidence of substantial publication bias ( P  = .73, P  = .08).…”
Section: Resultsmentioning
confidence: 52%
“…No significant difference was observed between groups (RR = 1.20; 95% CI, 0.24 to 6.00; P  = .82; I 2  = 37.5%) (Figure 6). Omitting Lee et al [33], this result was similar (RR = 1.53; 95% CI, 0.23 to 10.12; P  = .66; I 2  = 45.1%). By Begg's and Egger's tests, there was no evidence of substantial publication bias ( P  = .73, P  = .08).…”
Section: Resultsmentioning
confidence: 52%
“…31,32 We implanted the Implantable Collamer Lens pIOL in patients with previous RD and found favorable outcomes without serious complications (data not shown). As comparative clinical studies of the Artisan/toric Artisan pIOLs versus Implantable Collamer Lens/toric Implantable Collamer Lens pIOLs were similar in terms of the ability to correct refractive error, 33,34 the Implantable Collamer Lens pIOL is expected to be a useful option.…”
Section: Discussionmentioning
confidence: 98%
“…Iris-claw fixated pIOLs are especially attractive as toric models because they are more rotationally secure in the anterior chamber are than haptic supported pIOLs. However, a toric sulcus pIOL produced significantly better uncorrected visual acuity than an iris-fixated pIOL in a recent study, which is discussed below in the comparison section [15].…”
Section: Iris-claw Fixated Anterior Chamber Phakic Iolsmentioning
confidence: 88%
“…Hassaballa et al [22] showed that the Visian ICL sulcus pIOL and Artisan iris-claw pIOL display equal and comparable safety, predictability, and efficacy. Lee et al [15] compared visual outcomes in patients receiving one of two toric pIOLs, the Visian toric ICL or the Artisan toric pIOL. They found similar correction of refractive error with both lenses, but logMAR uncorrected visual acuity was significantly higher in the Visian toric ICL group at 1, 3, and 6 months postoperatively.…”
Section: Phakic Iol Comparisonmentioning
confidence: 99%